Primary Immune Regulatory Disorders and Targeted Therapies - KOLUKISA, BURCU; BARIŞ, SAFA (GALENOS YAYINCILIK, 2021)
Primary immune regulatory disorders (PIRDs) are a group of diseases belonging to inborn errors of immunity. They usually exhibit lymphoproliferation, autoimmunities, and malignancies, with less susceptibility to recurrent infections. Unlike classical primary immune deficiencies, autoimmune manifestations, such as cytopenias, enteropathy can be the first symptom of diseases, and they are typically resistant to treatment. Increasing awareness of PIRDs among specialists and a multidisciplinary team approach would provide early diagnosis and treatment that could prevent end-organ damage related to the diseases. In recent years, many PIRDs have been described, and understanding the immunological pathways linked to these disorders provides us an opportunity to use directed therapies for specific molecules, which usually offer better disease control than known classical immunosuppressants. In this review, in light of the most recent literature, we will discuss the common PIRDs and explain their clinical symptoms and recent treatment modalities.
Keywords: Primary immune deficiencies; Immune dysregulation; Autoimmunity; Lymphoproliferation; Precision medicine; Targeted therapy; OF-FUNCTION MUTATIONS; MACROPHAGE ACTIVATION SYNDROME; 3-KINASE DELTA SYNDROME; SIGNAL TRANSDUCER; HEMOPHAGOCYTIC LYMPHOHISTIOCYTOSIS; COMBINED IMMUNODEFICIENCY; GERMLINE MUTATIONS; CTLA-4 CHECKPOINT; LRBA DEFICIENCY; DYSREGULATION